VidOCR a system for finding text embedded in outdoor images - Bungabong, Rhea (2000)
This paper deals with the detection, extraction and recognition of characteristics in general backgrounds particularly in images cpatured through video. Detection is where the images are segmented for the proper selection of possible text areas or regions within the images. When the candidate text areas are determined, these regions are bounded in boxes and saved as separate images. They are then binarized and filtered for recognition. Recognition is when the system is already able to read the texts or characters found in the images. Here, the binarized images are fed into an OCR (Optical Character Recognition) engine. The images used for this algorithm are first conveyed into gray scale images. The algorithm is efficient and works well on images of outdoor scenes. Examples are billboards, photographs and road signs. In this particular project, we used the nameplates of the different buildings around the university for our test images. These are the signs we see in yellow, blue and green backgrounds.